PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN WISATAWAN MENGUNJUNGI OBYEK WISATA PANTAI PANJANG KOTA BENGKULU - Setiadi, Yulius Wahyu; Fitri, Marliza Ade (JURNAL EKOMBIS REVIEW, 2018)
Target of which wish to be reached from this research is to know influence of the Service Marketing Mix toward tourist decision to visit Pantai Panjang in Bengkulu City. Research represent type research of survey that is research taking sample from a population and use questionnaire as a means of compiler of the data. The data was used obtained primary data pass questionnaire distribution. Population in this research is tourist which a visit to Pantai Panjang Bengkulu. The method of intake sample was used total sampling technique equal to 100 respondents. The method of the data analyze was used descriptive statistic and simple regression linear analysis. Pursuant to result of research known that : (1) Equation of obtained regression from result of data analysis is Y = 11,012 + 0,227Xthe meaning that if service marketing mix (physical evidence, process, and people) is goodness, hence decision of tourist visiting to Pantai Panjang more higher equal to 0,227; (2) The correlation coefficient (R) equal to 0,770; meaning the correlation between the service marketing mix (physical evidence, process, and people)with decision of tourist to visiting the Pantai Panjang is strength; (3) Value coefficient of multiple determination (R 2 ) is 0,593; meaning that decision of tourist to visiting the Pantai Panjang equal to 59,3% influenced by the service marketing mix (physical evidence, process, and people) anda while the rest 40,7% influenced by other factor which do not check; (4) From result of hypothesis test, proven that the service marketing mix (physical evidence, process, and people) have an effect on significant toward decision of tourist to visiting the Pantai Panjang, proved with significant value 0,007 < 0,05.